Spatial and temporal heterogeneity in the Jurumirim Reservoir, São Paulo, Brazil - Nogueira, M. G. [UNESP]; Henry, R. [UNESP]; Maricatto, F. E. [UNESP] (Wiley, 1999)
Jurumirim is a large tropical reservoir with remarkable spatial gradients. This structure seems to be determined by a longitudinal gradient in the trophic conditions along the main axis of the reservoir. Nutrient-rich waters enter from the main tributary river, Paranapanema, and towards the dam there is a lacustrine zone that is deeper and more oligotrophic. Additional variability is derived from two important lateral components: the entrance of the Taquari River, the second largest tributary, bringing waters with higher pH and alkalinity; and the Ribeirão das Posses arm, a sheltered bay where the hydrodynamic conditions promote a high growth of phytoplankton. However, such a spatial pattern is not static. It can become either more defined, during the dry season (late autumn and winter), or less evident, during the expansion of the lotic conditions in the rainy period (late spring and summer). Seasonal processes of stratification/destratification determine the temporal changes in the lacustrine zone but, unlike the upstream regions, the dam zone of the reservoir seems to be little affected by periodic pulses of modifications produced by intensive rains. The presence of extensive wetlands and oxbow lagoons in the mouth zones of the main rivers also constitutes an important source of spatial variability and should be considered in the future.
Keywords: Limnological variables; Seasonal pulse effect; Spatial organization; Tropical reservoir; limnology; reservoir; spatial variation; stratification; temporal variation; heterogeneity; lacustrine environment; trophic conditions; Brazil